A Halogen‐Free and Flame‐Retardant Sodium Electrolyte Compatible with Hard Carbon Anodes. Issue 23 (22nd October 2021) - Colbin, Lars Olow Simon; Mogensen, Ronnie; Buckel, Alexander; Wang, Yong‐Lei; Naylor, Andrew J.; Kullgren, Jolla; Younesi, Reza
Abstract: For sodium‐ion batteries, two pressing issues concerning electrolytes are flammability and compatibility with hard carbon anode materials. Non‐flammable electrolytes that are sufficiently stable against hard carbon have—to the authors' knowledge—previously only been obtained by either the use of high salt concentrations or additives. Herein, the authors present a simple, fluorine‐free, and flame‐retardant electrolyte which is compatible with hard carbon: 0.38 m sodium bis(oxalato)borate (NaBOB) in triethyl phosphate (TEP). A variety of techniques are employed to characterize the physical properties of the electrolyte, and to evaluate the electrochemical performance in full‐cell sodium‐ion batteries. The results reveal that the conductivity is sufficient for battery operation, no significant self‐discharge occurs, and a satisfactory passivation is enabled by the electrolyte. In fact, a mean discharge capacity of 107 ± 4 mAh g −1 is achieved at the 1005th cycle, using Prussian white cathodes and hard carbon anodes. Hence, the studied electrolyte is a promising candidate for use in sodium‐ion batteries. Abstract : A new fluorine‐free, flame‐retardant electrolyte consisting of triethyl phosphate and sodium bis(oxalato)borate is studied for sodium‐ion batteries. Relevant physical properties of the electrolyte obtained by combined experimental and computational methods are reported. Electrochemical and surface measurements indicate promising performance for the electrolyte in full‐cells of hard carbon anodes and Prussian white cathodes—a step towards safer and better batteries.